2017
DOI: 10.1159/000480208
|View full text |Cite
|
Sign up to set email alerts
|

Time to Transcatheter Arterial Chemoembolization Refractoriness in Patients with Hepatocellular Carcinoma in Kinki Criteria Stages B1 and B2

Abstract: Background: Transarterial chemoembolization (TACE) is recommended for patients with hepatocellular carcinoma (HCC) in Barcelona Clinic Liver Cancer (BCLC) stage B. However, because of the heterogeneity of HCC in BCLC stage B; various subclassification systems have been proposed to predict the prognosis of patients. Previously, we proposed the Kinki criteria for precise classification of HCC cases in BCLC stage B. In this study, we compared the time to TACE refractoriness in HCC patients with Kinki criteria sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 38 publications
4
55
1
Order By: Relevance
“…These results confirm the robustness of the concept of TACE refractoriness as defined by treatment guidelines. [6,7] In keeping with previous Japanese studies [19,20,22] we found a deterioration of liver function in patients that were refractory to TACE. However, the degree of deterioration was not significant in our study, possibly because TACE refractoriness was defined as progression after two sessions of TACE.…”
Section: Plos Onesupporting
confidence: 90%
“…These results confirm the robustness of the concept of TACE refractoriness as defined by treatment guidelines. [6,7] In keeping with previous Japanese studies [19,20,22] we found a deterioration of liver function in patients that were refractory to TACE. However, the degree of deterioration was not significant in our study, possibly because TACE refractoriness was defined as progression after two sessions of TACE.…”
Section: Plos Onesupporting
confidence: 90%
“…Hepatocellular carcinoma which is out of the up-to-7 criteria can be more aggressive than the 1 that is within. Arizumi et al [23] reported that TACE refractoriness occurred earlier in hepatocellular carcinomas that were out of the up-to-7 criteria than those within the up-to-7 criteria. Although the up-to-7 criteria were not useful for discriminating between TACE effectiveness Dig Dis 2018;36:385-394 DOI: 10.1159/000489488 and refractoriness, it would possibly be predictive of the TACE refractoriness if more patients were studied.…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Society of Hepatology tentatively defines TACE refractoriness based on the effect of two consecutive TACE procedures in reference to expert consensus, although the criteria for TACE refractoriness have not been definitively established in other countries . Several studies have assessed the definition of TACE refractoriness as adequate for clinical criteria . Factors, such as the viable tumor number and size targeted for TACE before the initial TACE procedure or during early TACE sessions, have been found to predict the probability of TACE refractoriness .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]8 Several studies have assessed the definition of TACE refractoriness as adequate for clinical criteria. 9,10 Factors, such as the viable tumor number and size targeted for TACE before the initial TACE procedure or during early TACE sessions, have been found to predict the probability of TACE refractoriness. [9][10][11][12] Nevertheless, no useful markers have been confirmed to predict TACE refractoriness.…”
Section: Introductionmentioning
confidence: 99%